Monitoring foodborne pathogens of food served at an institutional cafeteria - Qadreyah Almatawah; Salwa Al-Mutairi; Julie Varghese (Applied Food Research)
The provision of food by cafeterias is an opportunity to promote health through a balanced diet and safe food, offering the prospect of sustainably developing the well-being a community and the local economy. This study assessed the hygiene conditions of an institutional cafeteria. The presence of foodborne pathogens and indicators of general hygiene in 143 food and environmental samples were analyzed using the TEMPO and VIDAS food safety testing machines. All food samples tested negative for Salmonella sp., and Staphylococcus aureus counts were below the GCC Standardization Organization (GSO) limit. Escherichia coli was detected at level above the set limit in six food samples. Sixteen food samples showed aerobic bacterial counts above the set limit. Total coliforms and Enterobacteriaceae were each detected above the set limits in eight food samples. Yeasts and molds were detected above the set limit in 14 food samples. Coliform bacteria, S. aureus, and mold were detected on the hands and white coats of cafeteria workers and on work surfaces, machines, and cutting boards. The hygiene conditions of the cafeteria are not suitable for food preparation, and to improve hygienic conditions in cafeterias, regular inspection of food and food preparation facilities is strongly recommended.